The Burden of Erectile Dysfunction in CKD: Exploring Etiology and Treatment Approaches - Khan, Mahnoor Alam; Naeem, Arooba; Zareen Ullah,; Khan, Aimal; Ali, Zafar; Noor, Khushbakht (Indus Journal of Bioscience Research, 2024)
Background: Erectile dysfunction (ED) is a common complication among chronic kidney disease (CKD) patients, severely affecting quality of life. Understanding its etiology and finding effective treatment approaches can improve patient outcomes. Aim: This study investigates the prevalence and contributing factors of ED in CKD patients while evaluating potential treatment options. Methods: This cross-sectional study was conducted at Nephrology Division, Khyber Teaching Hospital, Peshawar, from January to June 2024. Data were collected from male CKD patients aged 18 and above undergoing dialysis for at least six months. Patients with psychological or urological conditions unrelated to CKD were excluded. The International Index of Erectile Function (IIEF) and medical records were used to assess the prevalence of ED and contributing factors. Results: A total of 200 male patients participated, with 55% reporting ED. Hypertension (40%), diabetes (35%), hormonal imbalances (25%), and psychological issues (30%) were the primary contributing factors. Treatment options, including PDE5 inhibitors and lifestyle changes, improved sexual function in 45% of patients. Conclusion: ED is highly prevalent in CKD patients due to a combination of physiological and psychological factors. A multidisciplinary approach involving medical treatment, psychological support, and lifestyle modifications is critical.